Condition Monitoring of Bituminous Pavements Subjected to Repeated Dynamic Aircraft Loading - Kasthurirangan Gopalakrishnan (The Baltic Journal of Road and Bridge Engineering)
The Heavy Weight Deflectometer (HWD) is one of the most commonly used devices for monitoring the structural condition of airport pavement infrastructure systems on a routine basis in a rapid and non-destructive manner. The HWD measures pavement surface response (ie deflections) to an applied dynamic load that simulates a moving wheel of an aircraft at moderate speeds. The pavement surface deflection basins obtained by the HWD tests is frequently used as an indicator of the load-bearing capacity of the pavement. These tests were conducted on flexible test pavements at the US Federal Aviation Administration’s National Airport Pavement Test Facility (NAPTF) at various times to monitor the effect of simulated Boeing 777 and Boeing 747 aircraft gear trafficking on pavement structural condition. Multi-Depth Deflectometers (MDDs) installed within the pavement sections recorded the load-induced displacements in the pavement and in the subgrade. In this paper, the variations in HWD surface deflections acquired at different stages of NAPTF trafficking are compared with the MDD resilient displacements obtained under multiple-wheel heavy aircraft gear trafficking as well as with the periodic rut depth measurements. The results demonstrate the usefulness of routinely collected HWD surface deflection basins for reliable evaluating the structural performance of airport flexible pavements.